Happiness - Badiou, Alain (Bloomsbury Academic, 2019)
"'All philosophy is a metaphysics of happines...or it's not worth an hour of trouble' claims Alain Badiou in this lively intervention into one of the most persistent themes in philosophy: what is happiness? And what do I need to do to be happy? The desire to be happy is one of our most universal goals and yet there doesn't seem to be any easy answers or formulas for achieving happiness. And the concept has become so commodified and corrupted to be almost unrecognizable as something worth pursuing. In light of this, should we just give up the aspiration to be happy altogether? Alain Badiou thinks not. While eschewing futile procedures for magically becoming 'happy', Badiou does passionately maintain that in order to be truly happy we need philosophy. And, bolder still, that a life lived philosophically is the happiest life of all!"--Provided by publisher.